Immunity to the Dual Threat of Silica Exposure and Mycobacterium tuberculosis - Konečný, Petr; Ehrlich, Rodney; Gulumian, Mary; Jacobs, Muazzam (Frontiers in Immunology, 2019)
Exposure to silica and the consequent development of silicosis are well known health problems in countries with mining and other dust producing industries. Apart from its direct fibrotic effect on lung tissue, silica’s chronic and immunomodulatory character causes susceptibility to tuberculosis (TB) leading to a significantly higher TB incidence in silica-exposed populations. The presence of silica particles in the lung and silicosis may facilitate initiation of tuberculous infection and progression to active TB, and exacerbate the course and outcome of TB, including prognosis and survival. However, the exact mechanisms of silica’s involvement in the pathological processes during mycobacterial infection are not yet fully understood. In this review, we focus on the host´s immunological response to both silica and Mycobacterium tuberculosis, on agents of innate and adaptive immunity, and particularly on silica-induced immunological modifications in co-exposure that influence disease pathogenesis. We review what is known about the impact of silica and Mycobacterium tuberculosis or their co-exposure on the host´s immune system, especially an impact that goes beyond an exclusive focus on macrophages as the first line of the defence. In both silicosis and TB, acquired immunity plays a major role in the restriction and/or elimination of pathogenic agents. Further research is needed to determine the effects of silica in adaptive immunity and in the pathogenesis of TB more generally.